2023
DOI: 10.18421/tem121-35
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Information Gain methods for Feature Selection in Distance Education Sentiment Analysis during Covid-19

Abstract: The disparities in access to public assistances between rural and urban areas are analyzed in this study, corresponding to the intensity in which the constructs are related to expected quality, perceived quality and perceived value as influential factors in citizen satisfaction and loyalty. In Guayaquil, a survey is carried out at the household level, 428 valid questionnaires are obtained in the rural area of Tenguel and 521 Valid questionnaires in the urban area of Tarqui, applyingto the American Customer Sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The results found that their approach yielded a higher accuracy for sentiment analysis, with an F1-score value of 0.945. Rijal et al [85] aimed to remove bias from sentiment analysis using concepts of feature selection. Their methodology involved the usage of the AdaBoost approach on the C4.5 method.…”
Section: Review Of Recent Work Related To Data Mining and Analysis Of...mentioning
confidence: 99%
“…The results found that their approach yielded a higher accuracy for sentiment analysis, with an F1-score value of 0.945. Rijal et al [85] aimed to remove bias from sentiment analysis using concepts of feature selection. Their methodology involved the usage of the AdaBoost approach on the C4.5 method.…”
Section: Review Of Recent Work Related To Data Mining and Analysis Of...mentioning
confidence: 99%